Inter-ELM evolution of the pedestal structures in type-I ELMy H-mode plasmas with LHW and NBI heating on EAST. (24th February 2017) - Han, X; Zang, Q; Xiao, S; Wang, T; Hu, A; Tian, B; Li, D; Zhou, H; Zhao, J; Hsieh, C; Li, M; Yan, N; et al.
Abstract: The evolution characteristics of type-I ELMy high-confinement mode pedestal are examined in EAST based on the recently developed Thomson scattering system. The influence of the plasma current on pedestal evolvement has been confirmed experimentally. In the higher I p case (500 kA) the pedestal height shows an increase trend until the onset of next ELM and in the lower I p cases (300 and 400 kA), however, this buildup saturates at the first ∼30% of the ELM cycle. In contrast, the width increases only during the first ∼70% of the ELM cycle and then keeps almost stable in three I p cases, but resulting in different widening size of ∼1.5, 1 and 0.5 cm for 300, 400 and 500 kA respectively. Experimental results show that the pedestal pressure width has good correlation with poloidal beta as Δ p e, ψ = 0.16 β p o l, where the fitting coefficient 0.16 is not changed with different plasma currents but a little larger than that of other machines. For each current level, the pedestal density increases while the pedestal temperature decreases. But with increasing I p platforms, the pedestal height prior to the ELM onset shows a near quadratic (within error bars) increase. Experimental measurements demonstrate that the decrease of Δ W E L M with increasing ν p e d * comes mostly from the reduction of the plasma temperature drop, while the pedestal density height keeps relatively stable. Additional injection of LHW has been proved to modify the pedestal structure which should be responsible for the remaining scatter of the experimental data.